A Window in Time: A Response to "Disorders of Temporality and The Subjective Experience of Time: Unresponsive Objects and the Vacuity of the Future" by Stephen Seligman. Issue 2 (3rd March 2016) - Harris, Adrienne; Bartlett, Robert
Abstract : This response to Stephen Seligman's "Disorders of Temporality and The Subjective Experience of Time: Unresponsive Objects and the Vacuity of the Future" considers Seligman's ideas in the context of field theory. Seligman's notion of becoming a self in time is elaborated through the concept, derived from field theory, of how time assumes an "essential ambiguity" that may facilitate analytic change and psychological development. This response suggests further that such "essential ambiguity" in relation to time opens both the patient and analyst up to a variety of complex, bidirectional influences, such as unconsciously mediated intergenerational transmissions of trauma. In addition, this response explores Seligman's ideas associated with an analyst's moment-to-moment recognitions and a patient's corresponding development of a self in time in terms of their implications for analytic participation and analytic self-care.